Evaluation of biochar from tea pruning residue and tea fluff compost utilization to alleviate soil chemical properties on an Inceptisol - Faris Nur Fauzi Athallah; Restu Wulansari (Journal of Degraded and Mining Lands Management, 2022)
The inorganic fertilizer that is used excessively in tea plantations causes soil health degradation. Tea pruning residue and tea fluff are local biomass that has the potential to be used as alternatives to soil nutrient input that is not well conducted in the tea plantation. This study evaluated biochar from the residue of tea pruning and tea fluff compost as potential organic materials to improve the chemical properties of soil in tea plantations. The tea pruning residue biochar and tea fluff compost were mixed in Inceptisols in a pot experiment with treatment combinations of A = control, B = 2.5 t manure compost/ha, C= 0.25% biochar + 1 t tea fluff compost/ha, D = 0.50% biochar + 1 t tea fluff compost/ha, E= 0.75% biochar + 1 t tea fluff compost /ha, F = 0.25% biochar + 1 t tea fluff compost/ha + 2.5 t manure compost/ha, G = 0.50% biochar + 1 t tea fluff compost/ha + 2.5 t manure compost/ha, and H = 0.75% biochar + 1 t tea fluff compost/ha + 2.5 t manure compost/ha. Soil incubation was conducted for 90 days, and soil samples were analyzed for pH, organic C, available P, exchangeable Mg, and exchangeable K contents. The results showed that the mixture of 0.50% biochar + 1 t tea fluff compost /ha + 2.5 t manure compost/ha gave the most optimal improvement in soil properties. The improvement percentages of soil properties obtained were available P of 334%, Exchangeable Mg of 38%, exchangeable K of 244% and pH of 4.6.